2015
DOI: 10.6018/analesps.31.3.173291
|View full text |Cite
|
Sign up to set email alerts
|

Victimización en la escuela: relación de la crianza y variables funcionales- disfuncionales del desarrollo

Abstract: Resumen: El presente estudio tiene como principal objetivo analizar el papel diferencial de la crianza (apoyo y comunicación versus control), de variables funcionales del desarrollo (empatía y mecanismos de afrontamiento funcionales) y las variables disfuncionales (inestabilidad emocional y afrontamiento improductivo) en la victimización ocurrida en el entorno escolar, o por el contrario, con el apego entre pares. Participaron en el estudio 418 alumnos, 224 chicas y 194 chicos adolescentes, entre 13 y 14 años,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
6

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 33 publications
0
11
0
6
Order By: Relevance
“…That is to say that the perception of support in this case serves on the one hand as a protective factor against emotional instability and on the other as a strengthening factor of empathic concern or concern others (Samper-García et al, 2015). This is not the case with adolescent offenders where parental support, especially from the father, is lower than that of non-offenders, accompanied by greater negligence and permissiveness, which is likely to diminish emotional development, causing the lack of support to directly affect a greater externalization of behaviors such as aggression (Gámez-Guadix et al, 2010; Mestre et al, 2010; Calvete et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…That is to say that the perception of support in this case serves on the one hand as a protective factor against emotional instability and on the other as a strengthening factor of empathic concern or concern others (Samper-García et al, 2015). This is not the case with adolescent offenders where parental support, especially from the father, is lower than that of non-offenders, accompanied by greater negligence and permissiveness, which is likely to diminish emotional development, causing the lack of support to directly affect a greater externalization of behaviors such as aggression (Gámez-Guadix et al, 2010; Mestre et al, 2010; Calvete et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…This fact highlights the importance of emotion regulation for psychological adjustment and for the quality of interpersonal relationships (Samper-García, Mestre-Escrivá, Malonda, & Mesurado, 2015). In addition, the development of emotional skills that are typical of EI (paying attention, understanding, and knowing how to manage emotions) can reduce the risk in adolescent cybervictims of eventually developing psychological problems as a consequence of cyberbullying (Extremera, Quintana-Orts, Mérida-López, & Rey, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The dimensional approach has also shown that both the use of psychological control and the lack of supervision by parents are risk factors that increase the likelihood of children bullying their peers or being victimized by them (Gómez-Ortiz et al 2016;Samper-García et al 2015;Holt et al 2008;Hong et al 2017). As for disclosure, it has been found that children who voluntarily confide in their parents and enjoy good communication with them, as well as those that grow up in a positive, warm, loving environment in which the child's autonomy is encouraged, are less likely to get involved in bullying and cyberbullying (Gómez-Ortiz et al 2014;Larrañaga et al 2016;Murphy et al 2017;Offrey and Rinaldi 2017;Stavrinides et al 2015;Fousiani et al 2016;Low and Espelage 2013).…”
Section: Introductionmentioning
confidence: 99%